Ovine mesenchymal stem cell chondrogenesis on a novel 3D-printed hybrid scaffold in vitro - De,Mori A; Heyraud,A; Tallia,F; Blunn,G; Jones,JR; Roncada,T; Cobb,J; Al-Jabri,T (Bioengineering, 2024)
This study evaluated the use of silica/poly(tetrahydrofuran)/poly(ε-caprolactone) (SiO2/PTHF/PCL-diCOOH) 3D-printed scaffolds, with channel sizes of either 200 (SC-200) or 500 (SC-500) µm, as biomaterials to support the chondrogenesis of sheep bone marrow stem cells (oBMSC), under in vitro conditions. The objective was to validate the potential use of SiO2/PTHF/PCL-diCOOH for prospective in vivo ovine studies. The behaviour of oBMSC, with and without the use of exogenous growth factors, on SiO2/PTHF/PCL-diCOOH scaffolds was investigated by analysing cell attachment, viability, proliferation, morphology, expression of chondrogenic genes (RT-qPCR), deposition of aggrecan, collagen II, and collagen I (immunohistochemistry), and quantification of sulphated glycosaminoglycans (GAGs). The results showed that all the scaffolds supported cell attachment and proliferation with upregulation of chondrogenic markers and the deposition of a cartilage extracellular matrix (collagen II and aggrecan). Notably, SC-200 showed superior performance in terms of cartilage gene expression. These findings demonstrated that SiO2/PTHF/PCL-diCOOH with 200 µm pore size are optimal for promoting chondrogenic differentiation of oBMSC, even without the use of growth factors.